POLITICAL LIBERALISM IN CANADA: THE CASE OF SYRIAN REFUGEES - Fahadayna, Adhi Cahya (Program Studi Hubungan Internasional, 2019)
The refugee crisis in Canada has to create the political dynamics caused by the ideological spectrum in Canadian Politics. Liberalism is the most widely accepted political ideology in Canadian. Refugee and political liberalism have been shared fundamental relations because political liberalism must oblige with humanity as its core value. Admittedly, political liberalism required a country or a government to fulfill its responsibility toward humanity by protecting or admitting refugees. Eventually, during the refugee crisis in Canada, political liberalism contributed a crucial role in the open-door policy toward refugees. This paper will focus on the crucial attesting role of political liberalism toward the open-door policy of the Canadian government toward refugees. Second, this paper also focuses on measuring the extent to which political liberalism widely accepted as a political ideology in Canada. Third, the paper also tries to discover the political justification of the open-door policy of Canada on the basis of political ideology. The paper will be using a literature study to explain the focuses of this paper.